Stéréotypes, idées reçues et lieux communs dans l’œuvre et la Correspondance de Gustave Flaubert - Rînciog, Diana (Romanica Silesiana, 2021)
Flaubert undeniably represents a fascinating case with regard to stereotyping, especially if one considers not only his masterpiece, Madame Bovary, but also his last volume, left unfinished in perhaps a symbolic way, Bouvard et Pécuchet, and the collections of clichés included in his Dictionnaire des idées reçues and Le Sottisier. What is prosaic is important for the novelist. Moreover, in his Correspondence we find a real and fascinating interest in the topic of the cliché. A key sentence concerning what is commonplace suggestively describes Charles Bovary’s conversation: “Charles’ conversation was as flat as a pavement, and people’s ideas paraded on it in their ordinary outfit, without vibrating with emotion, with laughter or with daydreaming” (my translation). Essentially, our aim is to dwell on language and gesture stereotypes as presented in some of Flaubert’s novels as well as in the short story Un cœur simple (A Simple Heart) and even in his travel notes. Furthermore, through the agency of Jean-Paul Sartre’s ample work L’Idiot de la famille (The Family Idiot), it is our aim to look into the language mechanisms which lead to mal du siècle in Flaubert’s view, namely the stupidity of wanting a conclusion and the circulation of received ideas.